2012
DOI: 10.1002/hed.21993
|View full text |Cite
|
Sign up to set email alerts
|

ACR appropriateness criteria® ipsilateral radiation for squamous cell carcinoma of the tonsil

Abstract: Patients that are appropriate for ipsilateral RT have less than 1 cm of tumor invasion into the soft palate or base of tongue, and nodal stage of N0 to 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…One difficulty in the published literature in relation to GA, lies with the lack of standardisation of assessment approaches to date (Puts et al, 2012). In the absence of evidence-based guidance, the Delphi method is frequently employed in healthcare to formulate expert consensus guidelines in a particular field (Simon et al, 2014, Uphoff et al, 2012, Yeung et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…One difficulty in the published literature in relation to GA, lies with the lack of standardisation of assessment approaches to date (Puts et al, 2012). In the absence of evidence-based guidance, the Delphi method is frequently employed in healthcare to formulate expert consensus guidelines in a particular field (Simon et al, 2014, Uphoff et al, 2012, Yeung et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…While low rates of contralateral neck failure with ipsilateral neck irradiation has been well established for patients with N0 or limited N1 nodal involvement, there is less data available for patients with advanced ipsilateral regional disease. Current consensus recommendations suggest bilateral prophylactic neck irradiation for nodal stage of N2b or higher due to theoretical concerns of altered lymphatic drainage patterns [1]. However, previously published data has suggested that the extent of primary tumor involvement may be more predictive of contralateral nodal failure [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…As for CTV, primary lesion with prophylactic bilateral levels II-IV was commonly included in N0 cases [ 58 ]. For N1 case a level V and supraclavicular region is recommend to be included.…”
Section: Early Stage Disease Stages I-iimentioning
confidence: 99%
“…The level V area can be excluded from the prophylactic nodal area in the case of N0 disease. Unilateral nodal CTV may be considered in early and intermediate-risk patients with favorable outcomes, such as those with localized TF lesions with T1-2 N0-1 [ 58 ].…”
Section: Clinical Target Volume (Ctv)mentioning
confidence: 99%